Study of electrical properties of CIGS thin films prepared by multistage processes (2010)
In this work, the dispersion mechanisms affecting the electric transport in CuIn1?xGaxSe2 (CIGS) thin films grown by a chemical reaction of the precursor species, which are evaporated sequentially in two and three-stage processes are analyzed. It was found, through conductivity and Hall coefficient measurements carried out as functions of temperature, that the electrical conductivity of the CuIn1?xGaxSe2 films is affected by the transport of free carriers in extended states of the conduction band as well as for variable range hopping transport mechanisms, each one predominating in a different temperature range.